Review of 1971/11/11 Concert at St. Francis Hall (University of Birmingham) Lunchtime concert of works by Christian Wolff, LaMonte Young, David Jones and Keith Potter - Friend, Howard C. (Contact: A Journal for Contemporary Music (1971-1990), 1971)
-